2014
DOI: 10.2337/dc13-1429
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Chronic Care Model in Small Medical Practices Improves Cardiovascular Risk but Not Glycemic Control

Abstract: OBJECTIVETo test whether the implementation of elements of the Chronic Care Model (CCM) via a specially trained practice nurse leads to an improved cardiovascular risk profile among type 2 diabetes patients. RESEARCH DESIGN AND METHODSThis cluster randomized controlled trial with primary care physicians as the unit of randomization was conducted in the German part of Switzerland. Three hundred twenty-six type 2 diabetes patients (age >18 years; at least one glycosylated hemoglobin [HbA 1c ] level of ‡7.0% [53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 36 publications
2
76
0
5
Order By: Relevance
“…This reality converges with international experiences, in countries that adopted a new specific care model for chronic conditions, which affirm their efficacy and efficiency to assist this population in its singular and plural aspects, expressed in their health-disease processes 6 , 20 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This reality converges with international experiences, in countries that adopted a new specific care model for chronic conditions, which affirm their efficacy and efficiency to assist this population in its singular and plural aspects, expressed in their health-disease processes 6 , 20 .…”
Section: Discussionmentioning
confidence: 58%
“…Starting from an important international discussion at the end of the 20 th century and the start of the 21 st century about health care models that take into account the needs of people with chronic conditions, new care models have been created, such as the Chronic Care Model 5 , developed in the United States, which has been widely used in different countries around the world, with reports of successful experiences 6 .…”
Section: Introductionmentioning
confidence: 99%
“…One such trial tested involvement of practice nurses and implementation of a chronic care model in patients with diabetes mellitus. 59 This approach is especially useful when the primary intervention involves a method of practice or a complex group of interventions that are testing different healthcare delivery strategies, and may be more efficient, simpler to execute, and less expensive than traditional individual patient randomization approaches.…”
Section: Cluster Randomization Trialsmentioning
confidence: 99%
“…Another study had similar findings that the sub-scales except for DSD demonstrated significant improvements in post-implementation ratings [31]. However, the program led by Frei et al found statistically significant differences in changes over time between intervention and control group patients in all CCM components, yet did not find statistically significant differences in changes between different components over time [45].…”
Section: Unique Contributions Of Ccm Components To Patient Carementioning
confidence: 83%
“…Among all the studies included in this review, six programs stated the absence of blinding or randomization [20,35,37,40,43,44]; four programs reported that the follow-up period was too short for the adequate detection of significant outcomes [24,38,45,46]; whilst three programs had a relatively small sample size [21,28,47]. Selection bias in patient recruitment includes differences in illness status [35], racial and cultural diversity [36,37,48], as well as in socioeconomic status [35].…”
Section: Discussionmentioning
confidence: 99%